1995
DOI: 10.22358/jafs/69807/1995
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bovine colostrum thermisation on immunoglobulin intestinal transfer in newborn lambs

Abstract: Experiment was carried out to test the influence of mixed bovine colostrum thermisation on immunoglobulin intestinal absorption in newborn lambs. Thirty-three newborn lambs were alloted to three treatments: free maternal suckling or three meals of pooled bovine colostrum (30/kg BW), given 0.5, 3.5 and 6.5 h after birth or three meals of the same but previously heated bovine colostrum. Gentle thermal treatment (62°C for 1 min.) was used in order to preserve immunoglobulin biological activity. Immunoglobulin G l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Inoculation of the digestive tract with intestinal bacteria can limit absorption (James et al, 1981). A similar type of result was observed by Bush et al (1982), who showed that pasteurisation of colostrum slightly improved absorption, however this was not confirmed by Grongnet et al (1996). Pasteurisation should be encouraged for other reasons and Li- Chan et al (1995) showed that careful treatment of Ig results in sufficient thermo-resistance.…”
Section: Diet Compositionmentioning
confidence: 70%
See 4 more Smart Citations
“…Inoculation of the digestive tract with intestinal bacteria can limit absorption (James et al, 1981). A similar type of result was observed by Bush et al (1982), who showed that pasteurisation of colostrum slightly improved absorption, however this was not confirmed by Grongnet et al (1996). Pasteurisation should be encouraged for other reasons and Li- Chan et al (1995) showed that careful treatment of Ig results in sufficient thermo-resistance.…”
Section: Diet Compositionmentioning
confidence: 70%
“…Balfour and Comline (1962) extracted a small molecular weight protein from colostrum which increased the absorption of Ig. However, Grongnet et al (1996) using a very similar protocol were not able to repeat the finding.…”
Section: Diet Compositionmentioning
confidence: 91%
See 3 more Smart Citations